Analysis of Influencing Factors of Acute Medication Poisoning in Adults in Emergency Department of Our Hospital from 2016 to 2019 and Observation of Curative Effect of Optimizing Emergency Procedures. (30th September 2021) - Bian, Wen; Zhu, Na; Han, Dong; Gu, Fang; Hu, Yiqian
Abstract : Objective . This study analyzed the influencing factors of acute medication poisoning in adults in the emergency department of our hospital from January 2016 to December 2019 and observed the curative effect of optimizing emergency procedures on adult acute medication poisoning. Our results showed that, among all acute drug poisoning patients, the most common poisoning drug was sleeping pills (24.22%), followed by painkillers (20.31%) and antipsychotics (16.41%). Education level, drug category, drug source, drug dosage, unknown drug composition, and medication side effect were all influencing factors of acute drug poisoning. High school education level or below, self-purchasing medicine, medication overdose, unknown drug composition, and medication side effect were the risk factors of acute medication poisoning. In addition, after the nursing management of optimizing emergency procedures for this type of patients, the rescue time, observation time, and hospital stay of the patients had been shortened, the incidence of complications was low, the rescue success rate was high, and the clinical application effect was good.